Characterisation of the Carpinus betulus L. Phyllomicrobiome in Urban and Forest Areas - Imperato, Valeria; Kowalkowski, Lukasz; Portillo-Estrada, Miguel; Gawronski, Stanislaw W.; Vangronsveld, Jaco; Thijs, Sofie (Frontiers in Microbiology, 2019)
Urban green areas are highly valued by citizens for their contribution to the quality of life in cities. Plants play an important role in mitigating airborne pollutants and are assisted in this role by the metabolic capacities of the millions of microbial cells that colonize leaf surfaces (phyllosphere). Many factors influence phyllosphere microbial community composition and function, but to what extent does airborne pollution in cities impact the composition of microbial communities and their functional degradation genes? Here we describe the characterization of the phyllospheric bacterial communities of Carpinus betulus L. trees (hornbeam) across three locations: the city center of Warsaw (Poland), a forest in a UNESCO World Heritage Site (Białowieża), and a forest in one of the world’s oldest operational oil fields (Bóbrka). C. betulus contained higher particulate matter (PM) concentrations, with higher concentrations of palladium and radon in the PM, on leaves in Warsaw than in the forests. Volatile organic compound (VOC) analyses of sampled air revealed higher concentrations of butanone methyl propanal, butylbenzene, and cyclohexane in Bóbrka than Warsaw and Białowieża, while in Warsaw, xylene and toluene were higher. Shotgun microbiome sequencing uncovered a dominance of Gammaproteobacteria (71%), mainly Pseudomonas spp., Actinobacteria, Alpha- and Betaproteobacteria, and Firmicutes. Community composition and function differed significantly between the forests and Warsaw city center. Statistically more hydrocarbon degradation genes were found in Białowieża compared to Warsaw and Bóbrka, and in vitro tests of diesel degradation and plant growth promotion traits of culturable representatives revealed that Białowieża held the highest number of bacteria with plant beneficial properties and degradation genes. This study provides the first detailed insights into the microbiome of C. betulus and sets the stage for developing to a more integrated understanding of phyllosphere microbiota in cities, and their relationships with human health.